Acute on Chronic Liver Failure From Nonalcoholic Fatty Liver Disease: A Growing and Aging Cohort With Rising Mortality. Issue 5 (25th March 2021) - Sundaram, Vinay; Jalan, Rajiv; Shah, Parth; Singal, Ashwani K.; Patel, Arpan A; Wu, Tiffany; Noureddin, Mazen; Mahmud, Nadim; Wong, Robert J.
Abstract : Background and Aims: We assessed the burden of nonalcoholic fatty liver disease (NAFLD)‐related acute on chronic liver failure (ACLF) among transplant candidates in the United States, along with waitlist outcomes for this population. Approach and Results: We analyzed the United Network for Organ Sharing registry from 2005 to 2017. Patients with ACLF were identified using the European Association for the Study of the Liver/Chronic Liver Failure criteria and categorized into NAFLD, alcohol‐associated liver disease (ALD), and hepatitis C virus (HCV) infection. We used linear regression and Chow's test to determine significance in trends and evaluated waitlist outcomes using Fine and Gray's competing risks regression and Cox proportional hazards regression. Between 2005 and 2017, waitlist registrants for NAFLD‐ACLF rose by 331.6% from 134 to 574 candidates ( P < 0.001), representing the largest percentage increase in the study population. ALD‐ACLF also increased by 206.3% (348‐1, 066 registrants; P < 0.001), whereas HCV‐ACLF declined by 45.2% ( P < 0.001). As of 2017, the NAFLD‐ACLF population consisted primarily of persons aged ≥60 years (54.1%), and linear regression demonstrated a significant rise in the proportion of patients aged ≥65 in this group (β = 0.90; P = 0.011). Since 2014, NAFLD‐ACLF grade 1 was associated with a greater risk of waitlist mortality relative to ALD‐ACLF (subhazard ratio [SHR] = 1.24; 95% confidence interval [CI], 1.05‐1.44) and HCV‐ACLF (SHR = 1.35; 95% CI, 1.08‐1.71), among patients aged ≥60 years. Mortality was similar among the three groups for patients with ACLF grade 2 or 3. Conclusions: NAFLD is the fastest rising etiology of cirrhosis associated with ACLF among patients listed in the United States. As the NAFLD population continues to grow and age, patients with NAFLD‐ACLF will likely have the highest risk of waitlist mortality.